The shugden-controversy in contemporary mongolia: preliminary findings from an exploratory field study - Batmunkh, Mungunchimeg 198X- (Inner Asia, 2021)
Since the political upheavals in Mongolia in 1989, the traditional Tibetan-Mongolian protective deity Dorj-Shugden has been rediscovered. Today the Buddhist monasteries Delgeriin khiid, Amarbayasgalant Monastery and Tögsbayasgalant töv venerate him. This paper analyses the role of this deity with particular emphasis on Gungaachoilinig datsan in Gandandegchilin and the Amarbayasgalant Monastery in Mongolia, based on ethnographic fieldwork and semi-structured interviews with monks from six monasteries and visitors of Amarbayasgalant conducted in 2016, 2019 and 2020. The paper also outlines the current state of research, including recent Mongolian literature. Finally, it presents findings about him sourced from social media. By exploring pro- and anti-Shugden religious practices, this article sheds some light on the Shugden controversy in contemporary Mongolian Buddhism.